ANALISIS MATERI AJAR IPA KIMIA SMP/MTs BERDASARKAN KURIKULUM 2013 - Dayanti, Pepi; Holiwarni, Betty; Haryati, Sri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The research subjects of science chemistry teaching of SMP / MTs are based on curriculum 2013. The object of this research is the science syllabus of SMP / MTs curriculum 2013. The research method used is descriptive, qualitative. This research uses Philip Mayring's analysis model starting from the research question stage, category determination or analysis center, step by step formulation of main category to sub category, revision of result of analysis (validation) and interpretation of result. The data collection instrument is a validation questionnaire given to 3 (three) validators, 2 lecturers of FKIP UR chemistry and 1 teacher of Raudatussalam Rambah School. Research shows that the results of the validation of the results of the analysis sheet amounted to 84.75% and are in a valid category. Based on the results of data analysis can be concluded that the subject matter of SMP / MTs chemistry is valid or in accordance with the curriculum 2013.Keywords: Analysis of teaching materials, Philip Mayring analysis model, Curriculum 2013, subject matter of SMP / MTs